2013
DOI: 10.1093/jac/dkt091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ertapenem use on Pseudomonas aeruginosa and Acinetobacter baumannii imipenem susceptibility rates: collateral damage or positive effect on hospital ecology?

Abstract: Use of ertapenem was directly associated with a downward trend in the use of imipenem and ciprofloxacin, which may have contributed to improve the susceptibility of P. aeruginosa to imipenem. Ertapenem use had no impact on the susceptibility of A. baumannii to imipenem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
2
20
0
3
Order By: Relevance
“…However, isolation rates of CRAB increased continuously during the implementation of the antibiotic-stewardship program. Similarly, a statistically significant reduction in CRAB rates was not observed previously following the implementation of a comprehensive antibiotic-stewardship program [15], [22], [26]. These findings suggest that the development of antibiotic resistance is multifactorial.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, isolation rates of CRAB increased continuously during the implementation of the antibiotic-stewardship program. Similarly, a statistically significant reduction in CRAB rates was not observed previously following the implementation of a comprehensive antibiotic-stewardship program [15], [22], [26]. These findings suggest that the development of antibiotic resistance is multifactorial.…”
Section: Discussionmentioning
confidence: 46%
“…This study, like previous studies, demonstrated an association between the increased use of Group 2 carbapenems and increased rates of CRAB isolates; by contrast, no statistically significant association was observed between the consumption of ertapenem and the rates of CRAB isolates [16], [24], [25]. These findings suggest that ertapenem use did not affect the cross-resistance of nonfermentative gram-negative bacilli to Group 2 carbapenems, and this had a positive impact on the hospital ecology by suppressing the selection pressure exerted by Group 2 carbapenems [14], [26].…”
Section: Discussionmentioning
confidence: 83%
“…En varios estudios contemporáneos se ha evaluado el impacto del uso de ertapenem en la emergencia de microorganismos resistentes y, aunque los resultados son contradictorios, la mayoría de los hallazgos apuntan a que no hay asociación (12,23). En el estudio de Sousa, et al, su empleo se relacionó con un menor uso de imipenem y con la mayor sensibilidad de P. aeruginosa a este medicamento (24 El uso de quinolonas fue otro factor de riesgo estadísticamente significativo en este estudio, al igual que en otras investigaciones y en un metaanálisis (OR=2,73; IC 95% 1,27-5,87) (25). Se ha observado que las concentraciones inhibitorias de ciprofloxacina crean una presión de selección a favor de mutantes con un incremento en la expresión del adenosín monofosfato (AMP) cíclico (26), mientras que los niveles no inhibidores incrementan la frecuencia de la mutación de resistencia a carbapenémicos mediante el aumento de la regulación de la bomba de flujo MexEFOprM y a niveles reducidos de la porina OprD, lo que afecta especialmente a meropenem y, probablemente, es el mecanismo que mejor explica esta resistencia inducida (27).…”
Section: Discussionunclassified
“…In fact, several studies suggest that ertapenem is not associated with increased carbapenem resistance in P. aeruginosa (25,26); however, these reports drew their conclusions from ecological analyses. Other studies have examined the effect of introducing ertapenem into a hospital on the susceptibility of P. aeruginosa to group 2 carbapenems (27,28); in these studies, the authors suspected that the improved susceptibility of P. aeruginosa to group 2 carbapenems was related to decreased fluoroquinolone use. However, in line with our finding, a recent patient-centered analysis provided a possible association of ertapenem with the appearance of P. aeruginosa resistance patterns (9).…”
Section: Discussionmentioning
confidence: 99%